Social construction of ATI and its influence on the choice of livelihood intervention by Process Foundation-Panay Inc. - Dela Vega, Anna Victoria M. (2016.)
In the Philippines, the Indigenous People?s Right Act or RA 9371 (IPRA) was passed in 1997 in order to address poverty and improve the lives of indigenous people. Hence, different livelihood support from government and non-government organizations emerged. However, despite of the effort from these sectors, there are still problems with regards to the sustainability of the given livelihood projects. The result of the study will provide ideas and information for non-government organizations in the possible assessment of projects in indigenous peoples? communities. This is a comparative study that examines the present status of indigenous peoples? (Ati) livelihood and how social construction of ?Ati? informs PROCESS Foundation Panay Inc. (NGO) Interventions to indigenous peoples? communities specifically in Brgy. General Fullon (Tina), Hamtic, Antique and Brgy. Poblacion Norte, Sitio Igcaputol, Tobias Fornier, Antique in terms of possible assessment of livelihood needs. This study used narrative analysis and participant observation in understanding and analyzing the similarities and differences on the social constructions. The gathered data were purely qualitative. The methods used in collecting data including key informant interview (KII), focus group discussion (FGD) and participant observation. Random sampling and purposive sampling were used in gathering the participants. The participants for FGD were chosen from the suggestion of the different tribal leaders in the respective Barangays and by the provincial manager for PFPI. The Barangay captains and tribal leaders were invited to answer the KII. Moreover, secondary data were used in order to supply additional information In this study the perceptions towards Ati is evident in the planning of projects by the external NGO. Because of these generalizations of Ati, the organization creates activities or support that can establish a change in behaviour. In contrast, both Brgy. General Fullon and Sitio Igcaputol did not consider social construction as one of the underlying factors that can affect the intervention of external NGOs. Similarities and differences of social construction were drawn from the study. The willingness of both Ati communities to receive any kind of livelihood project is evident and both think that they are capable enough to do the project that will be offered to them. On the side of Process Foundation, they still follow a part of their policy where they train benefactors to increase their capability or skills to further excel in their livelihood project given. However, although there were various trainings conducted by the organization, the present livelihoods of both Ati communities are still poor. Aside from the social construction, other factors such as language must be considered. Language plays an important role in the communication of the community with the external environment. In the study, no staff from the PROCESS Panay knows ?inati?. Since the medium of instruction are Kinaray-a, Tagalog, or English, this may affect the exchange of information from the NGO and indigenous people?s communities
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Ati -- Livelihood; Process Foundation